2022
DOI: 10.1002/cld.1197
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Hepatitis B and C Virus Infections Among Rohingya Refugees in Bangladesh: A Growing Concern for the Refugees and the Host Communities

Abstract: Content available: Audio Recording

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Only 13% of HBV‐negative individuals had completed HBV immunization, of which 89% were children under 8 years of age 43 . A recent study amongst 2000 Rohingya refugees in Cox's Bazaar in Bangladesh found a prevalence of 4% 44 . Another study of Rohingya refugees in Cox's Bazaar evaluated causes of 272 cases of acute jaundice, reporting 13% were positive for hepatitis B 45 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 13% of HBV‐negative individuals had completed HBV immunization, of which 89% were children under 8 years of age 43 . A recent study amongst 2000 Rohingya refugees in Cox's Bazaar in Bangladesh found a prevalence of 4% 44 . Another study of Rohingya refugees in Cox's Bazaar evaluated causes of 272 cases of acute jaundice, reporting 13% were positive for hepatitis B 45 .…”
Section: Resultsmentioning
confidence: 99%
“…The wide range of results reflects differences in study design and quality, and that hepatitis B prevalence varies on national and subnational levels. 1 It also highlights the diversity of refugee populations, whose health status and access to health care may be influenced by differences in living conditions, health systems in their country of origin and country of current residence and exposure to varying risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, millions of Rohingya refugees fled from Myanmar in the last 50 years, and an estimated 1.4 million refugees are seeking asylum in Bangladesh, India, Indonesia, Nepal, Thailand, and Malaysia (Bearak, 2017;Rashid et al, 2017;UN News, March 2022). Pneumonia, liver diseases, breathing difficulties (Ismail et al, 2022); diphtheria, HIV, sexually transmitted diseases, Covid-19 (Mohiuddin, 2020b); Hepatitis B and C (Ali et al, 2022) have so far reported among refugees. The forced migration has created anxiety, depression, emotional distress, and PTSD among more than 60% of them (Palit et al, 2022).…”
Section: [6] Myanmar Military Vs Arakan Armymentioning
confidence: 99%
“…However, millions of Rohingya refugees fled from Myanmar in the last 50 years, and an estimated 1.4 million refugees are seeking asylum in Bangladesh, India, Indonesia, Nepal, Thailand, and Malaysia (Bearak, 2017;Rashid & Iqbal, 2017;UN News, 2022a). Pneumonia, liver diseases, breathing difficulties (Ismail et al, 2022); diphtheria, HIV, sexually transmitted diseases, COVID-19 (Mohiuddin, 2020b); Hepatitis B and C (Ali et al, 2022) have so far reported among refugees. The forced migration has created anxiety, depression, emotional distress, and PTSD among more than 60% of them (Palit et al, 2022).…”
Section: Myanmar Military Vs Arakan Armymentioning
confidence: 99%